CITRA MEREK, KUALITAS PRODUK, KERAGAMAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK “MAYBELLINE” DI MISS GLAM GUNUNG PANGILUN PADANG - Audri, Regina; Magdalena, Maria (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This study aims to analyze the influence of brand image, product quality, and product diversity on the purchase decision of Maybelline cosmetic products in Miss Glam Gunung Pangilun Padang. Data were collected through surveys using questionnaires administered to 89 respondents who are consumers of Maybelline cosmetic products, utilizing accidental sampling technique. Data analysis was conducted using descriptive statistical methods and multiple linear regression, while hypothesis testing utilized t-statistic tests. The results of the study indicate that: 1) Brand image has a positive and significant influence on the purchase decision of Maybelline cosmetic products. 2) Product quality has a positive and significant influence on the purchase decision of Maybelline cosmetic products. 3) Product diversity has a positive and significant influence on the purchase decision of Maybelline cosmetic products. The practical implications of this research emphasize the importance of efforts to strengthen brand image, improve product quality, and expand product diversity as marketing strategies to increase sales of Maybelline cosmetic products. This study contributes to the development of marketing strategies for cosmetic products in facing increasingly competitive market conditions.